2008
DOI: 10.1038/ajh.2008.243
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy Improves Arterial Stiffness in Primary Aldosteronism

Abstract: BackgroundAldosterone has been shown to substantially contribute to the accumulation of different types of collagen fibers and growth factors in the arterial wall, which increase wall stiffness. We previously showed that arterial wall stiffness is increased in primary aldosteronism (PA) independently of concomitant hypertension. This study was aimed at assessing the effects of specific treatment of PA on the arterial stiffness.MethodsTwenty-nine patients with confirmed PA (15 with aldosterone-producing adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 35 publications
1
60
0
2
Order By: Relevance
“…†Compared with 1 mo. by guest on May 11, 2018 http://hyper.ahajournals.org/ Downloaded from arterioles in our study). One reason for the lower EDV levels in the interlobar artery before surgery might be heightened vascular stiffness because of high levels of aldosterone.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…†Compared with 1 mo. by guest on May 11, 2018 http://hyper.ahajournals.org/ Downloaded from arterioles in our study). One reason for the lower EDV levels in the interlobar artery before surgery might be heightened vascular stiffness because of high levels of aldosterone.…”
Section: Discussionsupporting
confidence: 46%
“…One reason for the lower EDV levels in the interlobar artery before surgery might be heightened vascular stiffness because of high levels of aldosterone. It has been shown that adrenalectomy improves arterial stiffness in patients with PA. 18 In addition, because aldosterone constricts distal small arteries, such as glomerular afferent and efferent arterioles, 19,20 the lower EDV in the interlobar artery might be because of heightened downstream vascular resistance. We also observed that EDV decreased in the interlobar artery from 1 month to 12 months postoperatively, returning to the baseline level.…”
Section: Discussionmentioning
confidence: 99%
“…In a study reported by Tsuchiya et al (527), both unilateral adrenalectomy and spironolactone treatment led to improvements in endothelial function in patients with PA (which was worse than in essential hypertensives despite similar blood pressure levels on nonspecific antihypertensives). Strauch et al (504) reported unilateral adrenalectomy but not spironolactone to result in reduced arterial stiffness (measured as carotid-femoral pulse wave velocity and augmentation index) in PA patients studied ϳ1 yr following surgery or commencement of medical treatment. Catena et al (81) similarly found surgery but not spironolactone to result in significant reduction in left ventricular mass after one year.…”
Section: Effects Of Specific Treatment Against Aldosterone Excessmentioning
confidence: 99%
“…Those with long-term followup suggested that spironolactone provided the same effect, but more slowly [25]. Likewise, pulse-wave velocity and carotid intima-media thickness, which are increased in PA, improved after surgery [26,27] and spironolactone again provided the same benefit, but more slowly [28].…”
Section: Cardiovascular Renal and Metabolic Impact 231 Infraclinimentioning
confidence: 93%